The performance of tool holder clamping technique in conventional lathe with passive damping system - Gwee, Chiou Chin (2013)
There are various techniques proposed by some researchers to predict and detect the chatter where the objective is to prevent the occurrence of chatter in the cutting process to get a better surface finish product, higher productivity and tool life. These studies are mostly about active damping system by control the machining process parameters. Active damping techniques are not applicable under all circumstances because, for example, power requirements, cost, environment, etc. In those situations, the passive damping techniques are viable alternatives. Designed in passive damping for any structure is usually based on one of four damping mechanisms: viscoelastic materials, viscous fluids, magnetics or passive piezoelectric. Research on viscoelastic damping and other damping material in a lathe machine is hardly found. Thus, the relative influence of viscoelastic damping and softwood damping on conventional turning tool wear, tool vibration, and surface finish is investigated. The overall objective of this research is to evaluate the performance of new tool holder clamping technique by adding viscoelastic and softwood passive damping system for the application of conventional lathe machine. The specific objectives of the research are To evaluate the effectiveness of viscoelastic and softwood damping system in reducing tool wear during machining cold work tool steel AISI D2 of 45 HRC, To study the influence of clamping technique on tool vibration, and to study the effect of viscoelastic and softwood damping system on the surface finish. Nine set of experiments had been carried out during the experiment, three for each damping conditions: no damping, neoprene damping, and pine wood damping. Data obtained from experiment has been analysis by using ezANOVA software. As the summary of the experiment findings, neoprene damping shows extremely significant positive effect on the performance of machining of conventional lathe machines in tool wear and tool vibration. The attempt of using pine wood as damping material has result extremely significant lower tool vibration too. However, wood damping does not give significant effect on the tool wear and surface roughness.